Multi-Costs Evaluation for Logistics Value Chain in Vietnam: A Fuzzy AHP Approach - Do, Thi Thu Ha; Pham, Kien Van; Le, Na (ExcelingTech, 2020)
There is a paradox that Vietnam is becoming the leading country in the Southeast Asia region in terms of low-cost advantages. However, the logistics industry in Vietnam is not in this trend, because its costs are being evaluated as very high compared to other countries. Over the years, there have very few empirical studies focusing on this issue. In addition, the costs of logistics services are very diverse, but there is a lack of studies to assess these costs as a whole.Therefore, this paper aims to fill the mentioned research gaps by assessing the existing costs of logistics services in Vietnam. To accomplish this goal, the paper uses the concept of the logistics value chain (LVC) to systematically arrange costs and the Fuzzy-AHP (FAHP) method to measure the extent of the costs arising in the LVC. Based on the existing literature, four main costs and 14 sub-costs are selected to build the research model and questionnaire. A total of 20 experts are invited to participate in a face-to-face interview to evaluate the costs based on the pairwise comparison matrix.The findings show that costs incurred in the LVC are considered to be high in all four stages, of which procurement costs (C1) and production costs (C2) are the most concerns and need to be handled, while storage costs (C3) and transportation costs (C4) should be gradually improved in order to enhance the competitiveness of the logistics industry in Vietnam.Overall, the paper has contributed to supplementing the literature in the given field in terms of cost assessment in the LVC. Besides, the findings are also valuable references for managers to cut the logistics costs throughout the LVC.